Analysis of permanent magnet brushless AC motor using Fourier transform approach - Dwivedi A.; Singh S.K.; Srivastava R.K. (My University, 2025)
The paper presents an analytical model for determining performance characteristics of surface mountedpermanent magnet brushless motor using Fourier transform technique. The proposed scheme assumes a simplifiedgeometric model of surface mounted PM (SMPM) motor with dual current sheets using layer theory to analyseelectrical machines. The layer theory considers regions of PMBLAC motor to be replaced by layers of respectivehomogeneous material properties. Isotropic model assumes stator to be sloltless while anisotropic model is alsoconsidered to account for stator slotting effect on the motor performance. The Fourier transform applicable to linearinduction motor and introduced by S. Yamamura is modified and adapted for analysing PMBLAC motor. The primarystator winding and permanent magnets on rotor are replaced by their respective equivalent linear current densities.The proposed model is validated using experimental results from a 12-slot surface mounted PMBLAC motor. Theproposed method is capable of calculating the effect of design parameters on the performance of the SMPM motor,thus making it suitable for design and optimisation at initial stage. Moreover, analytical validation is also presented toprove the effectiveness of the proposed method. © The Institution of Engineering and Technology 2016.